Preparation method of platinum-lead alloy catalyst

By using the preparation method of platinum lead alloy catalyst in fuel cells, the problems of high stability and cost of platinum carbon catalysts are solved, and a catalyst with high activity, long life and low cost are achieved, which is suitable for fuel cell systems.

CN119208636APending Publication Date: 2024-12-27NORTHEASTERN UNIV CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411240064.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In traditional fuel cells, platinum carbon catalysts have problems such as low platinum dispersion, prone to agglomeration and inactivation, and carrier corrosion, resulting in poor catalyst stability and high cost, making it difficult to achieve large-scale application.

Method used

The preparation method of platinum-lead alloy catalyst is adopted. By introducing lead elemental substances on the support, mechanical ball milling is used to enhance the binding force between platinum and the support, prevent platinum agglomeration, and improve the dispersion of platinum and the stability of the support through reflux reaction.

Benefits of technology

It improves the activity and stability of the catalyst, reduces the use of platinum, extends the service life of the catalyst, and reduces production costs. It is suitable for fuel cell systems, especially in proton membrane exchange fuel cells and direct methanol fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
Patent Text Reader

Abstract

The invention relates to a preparation method of a platinum-lead alloy catalyst, which comprises the following specific steps: mixing soluble lead salt, a carrier material and a reducing agent in water according to a certain proportion, uniformly stirring, carrying out a reduction reaction at a certain temperature, and filtering, washing and drying to obtain a lead-containing carrier material after the reduction reaction is finished; then putting platinum metal salt, a lead-containing carrier material and a reducing solvent into a ball mill according to a certain proportion for mechanical ball milling, and after ball milling is finished, separating out feed liquid and grinding beads; adjusting the ground feed liquid to be alkaline, uniformly stirring and mixing, performing reflux reaction at a certain temperature, cooling to room temperature after the reaction is finished, adjusting the pH to be weakly acidic, standing, and washing and drying to obtain the platinum-lead alloy catalyst. The catalyst product provided by the invention has the advantages of high electrocatalytic activity, less noble metal consumption, long cycle service life, simple preparation conditions and the like, and solves the problems that the binding force between the carrier and platinum is poor and the carrier is easy to corrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalytic oxidation and relates to a method for preparing a platinum-lead alloy catalyst. Background Art

[0002] Traditional fossil energy sources cause serious environmental pollution. Hydrogen fuel cells have attracted much attention due to their advantages such as high calorific value, pollution-free and abundant hydrogen reserves. One of the core components of hydrogen fuel cells is the catalyst, and the most commonly used cathode and anode catalysts are Pt / C catalysts. Commercial carbon powder is widely used as a catalyst carrier due to its low cost and high mesoporous distribution, but carbon materials are prone to electrochemical corrosion (galvanic cell effect) as the catalytic reaction proceeds, resulting in catalyst deactivation. Secondly, platinum resources are scarce and expensive, and its cost accounts for about 40% of the total cost of fuel cells. The platinum-carbon catalysts currently used commercially have the disadvantages of low platinum dispersion and easy agglomeration and deactivation. Therefore, improving the activity and stability of fuel cell catalysts is of great value to the large-scale application of fuel cells.

[0003] There are many factors that affect the activity and stability of supported platinum catalysts, such as the particle size, structure, morphology, carrier type and loading rate of the platinum catalyst. The use of carbon-supported Pt-M alloy catalysts can effectively reduce the platinum loading rate and improve the stability of the catalyst. At present, the common preparation methods of Pt-M alloy catalysts include coprecipitation, microemulsion, impregnation, pyrolysis, physical reduction, etc. The equipment used in the coprecipitation method is expensive, the cost is high, and the precipitation conditions need to be precisely controlled. The microemulsion method and the impregnation method have poor metal applicability (precious metals) and require precise configuration of metal salt concentrations. The precursor synthesis in the pyrolysis method is difficult, and a high-temperature resistant catalytic carrier material needs to be selected. The physical reduction method has defects such as poor metal dispersion and harsh operating conditions, so it is difficult to realize the practical application of Pt-M alloy catalysts. Summary of the invention

[0004] Based on the above deficiencies in the prior art, the present invention provides a method for preparing a platinum-lead alloy catalyst, which mainly solves problems such as corrosion and stability of the carrier, and achieves the advantages of good activity, high stability and long service life of the platinum-based catalyst for fuel cells.

[0005] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing a platinum-lead alloy catalyst, characterized in that the method for preparing the platinum-lead alloy catalyst comprises the following steps:

[0006] S1. The soluble lead salt, the carrier material, the reducing agent A are mixed in water in a certain proportion, stirred evenly and then subjected to a reduction reaction at a certain temperature, and after completion, filtered, washed and dried to obtain a lead-containing carrier material;

[0007] S2. Platinum metal salt, lead-containing carrier material and reducing solvent B are placed in a ball mill in a certain proportion for mechanical ball milling. After the ball milling is completed, the feed liquid and the grinding beads are separated.

[0008] S3. Adjust the ground material liquid to alkaline, stir and mix evenly, and then reflux at a certain temperature. After the reaction is completed, cool to room temperature, adjust the pH to weak acidity, let it stand, and then wash and dry to obtain a sample material.

[0009] The soluble lead salt described in step S1 is one of soluble lead salts such as lead nitrate, lead acetate, and lead chloride.

[0010] The carrier material described in step S1 is one of materials such as carbon powder, carbide, nitride, transition metal, etc.

[0011] The reducing agent A described in step S1 is one or more reducing materials such as sodium hypophosphite, formaldehyde, ascorbic acid, formic acid, hexacarbonyl tungsten, sodium borohydride, etc.

[0012] The mass ratio of the soluble lead salt, the carrier material and the reducing agent A described in step S1 is (0.1-20):1:(1-50).

[0013] The reduction reaction conditions in step S1 are: temperature 70-100° C., time 0.5-4 hours, and stirring speed 200-600 rpm.

[0014] The reducing solvent B described in step S2 is one of organic substances such as ethylene glycol, acetaldehyde, formaldehyde, formic acid, methanol, ethanol, glycerol, etc.

[0015] The mass ratio of the platinum metal salt, the lead-containing carrier material and the reducing solvent B in step S2 is (0.1-10): 1:

[0016] (10 to 100). The platinum metal salt is one of soluble platinum salts such as chloroplatinic acid, potassium chloroplatinate, and ammonium chloroplatinate.

[0017] The mechanical ball milling conditions described in step S2 are: one of a horizontal ball mill or a vertical ball mill, a ball milling speed of 200 to 2000 rpm, a ball milling time of 0.5 to 48 hours, and a grinding bead diameter of 0.5 to 5 cm.

[0018] The reflux reaction conditions described in step S3 are: nitrogen or argon protection, pH value greater than 10, reflux temperature of 80-180° C., reflux time of 1-5 h, and 200-600 rpm.

[0019] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0020] 1. Introducing single lead onto the carrier before loading platinum can reduce the accelerated corrosion of platinum on the carrier during the use of traditional supported platinum catalysts and improve the stability of the carrier.

[0021] 2. Through the mechanical ball milling method, defects can be generated in situ on the lead-containing carrier by using mechanical force, and then the platinum precursor can be anchored on the lead carrier, thereby enhancing the bonding force between platinum, lead and the carrier and improving the stability of platinum.

[0022] 3. Direct pre-reduction and mechanical force through mechanical ball milling can effectively prevent platinum from agglomerating in the subsequent reduction process, making the platinum atoms highly dispersed, and achieving low platinum loading and high performance without volume amplification effect.

[0023] 4. The lead in the carrier is conductive, which can reduce the amount of precious metal platinum without affecting the service life and catalytic activity of the platinum-lead catalyst, thereby reducing the production cost of the electrode.

[0024] The platinum-lead alloy catalyst of the present invention is preferably used in a fuel cell system, and more preferably in a fuel cell including a proton membrane exchange fuel cell or a direct methanol fuel cell. The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification, and in order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description in combination with the preferred embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solution of the product of the present invention, the following is a brief introduction to the drawings of the present invention. The drawings and the following specific embodiments are used to explain the present invention, but do not constitute a limitation of the present invention.

[0026] Figure 1 Cyclic voltammograms of the platinum-lead alloy catalysts of Examples 1 to 4. The test conditions are: in an oxygen-permeable state, with 0.5 mol / L sulfuric acid as the electrolyte, and using a CHI660E electrochemical workstation for testing.

[0027] Figure 2 The platinum-lead alloy catalysts of Examples 1 to 4 are Figure 1 Comparison chart before and after 2000CV cycle scanning under test conditions. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.

[0029] The ranges and values ​​indicated herein are not limited thereto, and these ranges should be understood as values ​​that include and are close to these ranges or values. No substantial improvements or adjustments are made to the present invention and they still fall within the protection scope of the present invention.

[0030] The present invention will be described in detail below through examples. In the following examples, the electrochemical performance of the catalyst was measured by a CHI660E electrochemical workstation;

[0031] In the following examples, the present invention uses a 0.5 mol / L sulfuric acid solution as the electrolyte under oxygen conditions, uses a Pt|Hg(l)|Hg2Cl2(s)|KCl(saturated) electrode as the reference electrode, a platinum sheet electrode as the counter electrode, and a glassy carbon electrode as the working electrode in a three-electrode system, and the cyclic voltammetry curve of the catalyst is used as the evaluation standard for the catalyst stability. The instruments and drugs used in the examples were purchased through formal channels, and the specific manufacturers are not marked here.

[0032] Example 1

[0033] 0.1 g of lead nitrate, 1 g of acetylene black, and 1 g of formic acid (mass ratio of 0.1:1:1) were mixed in 50 mL of water, stirred evenly, and then reduced. The temperature was controlled at 70 ° C, the reaction time was 4 hours, and the stirring speed was 200 rpm. After the reaction, the lead-containing acetylene black carrier material was obtained by filtration, washing, and drying. 0.1 g of chloroplatinic acid, 1 g of the prepared lead-containing acetylene black carrier, and 50 g of ethylene glycol (mass ratio of 0.1:1:50) were placed in a ball mill for mechanical ball milling. The ball milling speed was controlled to 200 rpm, the ball milling time was 48 hours, and the diameter of the grinding beads was 5 cm. After the ball milling, the feed liquid and the grinding beads were separated. The pH value of the milled feed liquid was adjusted to be greater than 10, and after stirring and mixing evenly, a reflux reaction was carried out under nitrogen protection, and the reflux temperature was controlled to 80 ° C, the reflux time was 5 hours, and the stirring speed was 600 rpm. After the reflux reaction, it was cooled to room temperature, the pH was adjusted to weak acidity, and after standing, it was washed and dried to obtain the acetylene black-loaded platinum-lead catalyst A1.

[0034] Take 5 mg of catalyst A1, add 1 ml of isopropanol and 50 ul of nafion membrane solution to make a 5 mg / mL slurry, and take 10 ul of the slurry to test the electrochemical performance on a glassy carbon electrode. In this example, the range of the cyclic voltammetry curve test is 0.96 to -0.24 V, and the scan rate is 50 mv / s; the test range of the polarization curve test is 1 to 0 V, and the scan rate is 5 mv / s.

[0035] Example 2

[0036] 20 g of lead acetate, 1 g of titanium carbide, and 50 g of formaldehyde (mass ratio of 20:1:50) were mixed in 1000 mL of water, stirred evenly, and then reduced. The temperature was controlled at 100 ° C., the reaction time was 0.5 hours, and the stirring speed was 600 rpm. After the reaction was completed, the lead-containing titanium carbide carrier material was obtained by filtration, washing, and drying. 10 g of potassium chloroplatinate, 1 g of the obtained lead-containing titanium carbide carrier, and 30 g of formaldehyde (mass ratio of 10:1:30) were placed in a ball mill for mechanical Ball milling, control the ball milling speed to 2000rpm, the ball milling time to 0.5h, the grinding bead diameter to 0.5cm, and separate the feed liquid and the grinding beads after the ball milling; adjust the pH value of the milled feed liquid to be greater than 10, stir and mix evenly, and then reflux reaction under argon protection, control the reflux temperature to 180℃, the reflux time to 1h, and the stirring speed to 200rpm; after the reflux reaction is completed, cool to room temperature, adjust the pH to weak acidity, let it stand, wash and dry to obtain the titanium carbide-supported platinum-lead catalyst A2.

[0037] Take 5 mg of catalyst A2, add 1 ml of isopropanol and 50 ul of nafion membrane solution to make a 5 mg / mL slurry, and take 10 ul of the slurry to test the electrochemical performance on a glassy carbon electrode. In this example, the range of the cyclic voltammetry curve test is 0.96 to -0.24 V, and the scan rate is 50 mv / s; the test range of the polarization curve test is 1 to 0 V, and the scan rate is 5 mv / s.

[0038] Example 3

[0039] 10 g of lead chloride, 5 g of titanium nitride, and 50 g of ascorbic acid (mass ratio of 2:1:10) were mixed in 500 mL of water, stirred evenly, and then reduced at 85 ° C. The reaction time was 2.5 hours and the stirring speed was 355 rpm. After the reaction was completed, the lead-containing titanium nitride carrier material was obtained by filtration, washing, and drying; 1.5 g of ammonium chloroplatinate, 1 g of the obtained lead-containing titanium nitride carrier, and 10 g of methanol (mass ratio of 1.5:1:10) were placed in a ball mill for mechanical Ball milling, control the ball milling speed to 585 rpm, the ball milling time to 7.5 h, the grinding bead diameter to 3.2 cm, and separate the feed liquid and the grinding beads after the ball milling; adjust the pH value of the milled feed liquid to be greater than 10, stir and mix evenly, and then reflux reaction under nitrogen protection, control the reflux temperature to 125 ° C, the reflux time to 2.6 h, and the stirring speed to 502 rpm; after the reflux reaction is completed, cool to room temperature, adjust the pH to weak acidity, let it stand, and then wash and dry to obtain the titanium nitride-supported platinum-lead catalyst A3.

[0040] Take 5 mg of catalyst A3, add 1 ml of isopropanol and 50 ul of nafion membrane solution to make a 5 mg / mL slurry, and take 10 ul of the slurry to test the electrochemical performance on a glassy carbon electrode. In this example, the range of the cyclic voltammetry curve test is 0.96 to -0.24 V, and the scan rate is 50 mv / s; the test range of the polarization curve test is 1 to 0 V, and the scan rate is 5 mv / s.

[0041] Example 4

[0042] 1.8g of lead nitrate, 2g of tungsten powder, and 24g of reducing agent (the mass ratio of the three is 0.9:1:12), the composition of the reducing agent is 8g of sodium hypophosphite, 8g of hexacarbonyl tungsten and 8g of sodium borohydride, the materials are mixed in 600mL of water, stirred evenly and then reduced, the temperature is controlled at 88°C, the reaction time is 1.2 hours, the stirring speed is 465rpm, after the reaction is completed, the lead-containing tungsten carrier material is obtained by filtration, washing and drying; 0.75g of chloroplatinic acid, 1.5g of the prepared lead-containing tungsten carrier, 33g of acetaldehyde (the mass ratio is 0. 5:1:22) was placed in a ball mill for mechanical ball milling, the ball milling speed was controlled to be 1500 rpm, the ball milling time was 1.5 h, the diameter of the grinding beads was 3.7 cm, and the feed liquid and the grinding beads were separated after the ball milling; the pH value of the milled feed liquid was adjusted to be greater than 10, and after stirring and mixing evenly, a reflux reaction was carried out under argon protection, the reflux temperature was controlled to be 166° C., the reflux time was 2.9 h, and the stirring speed was 386 rpm; after the reflux reaction was completed, it was cooled to room temperature, the pH was adjusted to weak acidity, and after standing, it was washed and dried to obtain a tungsten-supported platinum-lead catalyst A4.

[0043] Take 5 mg of catalyst A4, add 1 ml of isopropanol and 50 ul of nafion membrane solution to make a 5 mg / mL slurry, and take 10 ul of the slurry to test the electrochemical performance on a glassy carbon electrode. In this example, the range of the cyclic voltammetry curve test is 0.96 to -0.24 V, and the scan rate is 50 mv / s; the test range of the polarization curve test is 1 to 0 V, and the scan rate is 5 mv / s.

[0044] In summary, by testing and drawing with an electrochemical workstation and comparing with the standard Pt / C 20% at the same platinum loading rate, it can be seen that the platinum-lead alloy catalyst obtained by the present invention has the advantages of high electrocatalytic activity, low precious metal usage, long cycle life, wide application range, high electrolysis efficiency, etc.

[0045] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any person skilled in the art can use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a platinum-lead alloy catalyst, characterized in that: The preparation method of the platinum-lead alloy catalyst comprises the following steps: S1. The soluble lead salt, the carrier material, the reducing agent A are mixed in water in a certain proportion, stirred evenly and then subjected to a reduction reaction at a certain temperature, and after completion, filtered, washed and dried to obtain a lead-containing carrier material; S2. Platinum metal salt, lead-containing carrier material and reducing solvent B are placed in a ball mill in a certain proportion for mechanical ball milling. After the ball milling is completed, the feed liquid and the grinding beads are separated. S3. Adjust the ground material liquid to alkaline, stir and mix evenly, and then reflux at a certain temperature. After the reaction is completed, cool to room temperature, adjust the pH to weak acidity, let it stand, and then wash and dry to obtain a sample material.

2. The method for preparing a platinum-lead alloy catalyst according to claim 1, characterized in that: The soluble lead salt described in step S1 is one of soluble lead salts such as lead nitrate, lead acetate, and lead chloride.

3. The method for preparing a platinum-lead alloy catalyst according to claim 1, characterized in that: The carrier material described in step S1 is one of materials such as carbon powder, carbide, nitride, transition metal, etc.

4. The method for preparing a platinum-lead alloy catalyst according to claim 1, characterized in that: The reducing agent A described in step S1 is one or more reducing materials such as sodium hypophosphite, formaldehyde, ascorbic acid, formic acid, hexacarbonyl tungsten, sodium borohydride, etc.

5. The method for preparing a platinum-lead alloy catalyst according to claim 1, characterized in that: The mass ratio of the soluble lead salt, the carrier material and the reducing agent A described in step S1 is (0.1-20):1:(1-50).

6. The method for preparing a platinum-lead alloy catalyst according to claim 1, characterized in that: The reduction reaction conditions in step S1 are: temperature 70-100° C., time 0.5-4 hours, and stirring speed 200-600 rpm.

7. The method for preparing a platinum-lead alloy catalyst according to claim 1, characterized in that: The reducing solvent B described in step S2 is one of organic substances such as ethylene glycol, acetaldehyde, formaldehyde, formic acid, methanol, ethanol, glycerol, etc.

8. The method for preparing a platinum-lead alloy catalyst according to claim 1, characterized in that: The mass ratio of the platinum metal salt, the lead-containing carrier material and the reducing solvent B in step S2 is (0.1-10):1:(10-100). The platinum metal salt is one of soluble platinum salts such as chloroplatinic acid, potassium chloroplatinate, and ammonium chloroplatinate.

9. The method for preparing a platinum-lead alloy catalyst according to claim 1, characterized in that: The mechanical ball milling conditions described in step S2 are: one of a horizontal ball mill or a vertical ball mill, a ball milling speed of 200 to 2000 rpm, a ball milling time of 0.5 to 48 hours, and a grinding bead diameter of 0.5 to 5 cm.

10. The method for preparing a platinum-lead alloy catalyst according to claim 1, characterized in that: The reflux reaction conditions described in step S3 are: nitrogen or argon protection, pH value greater than 10, reflux temperature of 80-180° C., reflux time of 1-5 h, and 200-600 rpm.